Wolff's headache and other head pain. - Wolff, Harold G. (Harold George), 1898-1962; Silberstein, Stephen D.; Lipton, Richard B.; Dalessio, Donald J., 1931- (Oxford University Press, 2001)
This text provides a comprehensive overview of headache disorders. The contributors are the acknowledged world leaders in their fields. This seventh edition reflects the enormous growth of knowledge regarding the classification of epidemiology, mechanisms, and treatment of headaches.